2019
DOI: 10.3390/medicina55010024
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Body Mass Index of Seven- and Eight-Year-Old Children, Dietary Behaviour and Nutrition-Related Parenting Practices

Abstract: Background and objective: Body mass index (BMI) is one of the key indicators used to measure the growth of children. It could be affected by the children’s nutrition, which is essential for the proper development of the child. Nutrition of children could be affected by many environmental factors, for example, the socioeconomic environment of the family. The aim of this study was to identify the associations between the BMI of seven- and eight-year-old children, dietary behaviour and nutrition-related parenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 52 publications
0
15
0
2
Order By: Relevance
“…A recent large-scale population study involving more than 250,000 children and adolescents suggested that current behaviors like television viewing and frequent nut consumption are more important predictors for BMI than early exposure to antibiotics, for example [ 68 ]. In addition, it has been shown that nutrition-related parenting practices were associated with BMI in children [ 69 ]. Finally, PA has been shown as a factor influencing BMI [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent large-scale population study involving more than 250,000 children and adolescents suggested that current behaviors like television viewing and frequent nut consumption are more important predictors for BMI than early exposure to antibiotics, for example [ 68 ]. In addition, it has been shown that nutrition-related parenting practices were associated with BMI in children [ 69 ]. Finally, PA has been shown as a factor influencing BMI [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…A further consideration is parental factors, which are known to be determinants of children's dietary patterns. Previous studies indicated that food practices [59], health concerns and parental BMI [60], and parenting styles [61,62] were associated with unhealthy dietary outcomes in children. Food environment at home and school are critical in the diet quality for school-aged children as their eating pattern are not self-sufficient [60,63,64].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…These studies recommended that reductions in weight and improvements in body composition can occur via consumption of healthy foods during school hours as well as by encouraging children to eat more healthy foods at home [ 18 , 19 , 37 41 ]. Also, nutritional based intervention programs have reported that plant-derived foods are effective in lowering body weight [ 42 ]. Moreover, current evidence suggests that carrying out a daily PA routine and eating a healthy diet positively influence cognitive and mental function in children [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%